PEMEROLEHAN BAHASA PADA ANAK USIA 3 TAHUN DITINJAU DARI SUDUT PANDANG MORFOSINTAKSIS - Adiprana Yogatama (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2011)
There is a close relationship between the structure of words and the structure of sentences. In some languages it is even difficult to tell whether a particular word formation is a word or a sentence. Language acquisition theory has advanced in many ways since Brown (1973), but we are still dealing with many of the same basic methodological issues he confronted. Elaborating on Brown’s approach, researchers have formulated increasingly reliable methods for measuring the growth of grammar, or morphosyntax, in child. In this paper, the writer tries to study the morphosyntax acquisition in Indonesian children age 3 years. This is a basic research before continuing the next study in children’s second language acquisition.